Long‐term enhancement of synaptic transmission between antennal lobe and mushroom body in cultured Drosophila brain. (25th October 2012) - Ueno, Kohei; Naganos, Shintaro; Hirano, Yukinori; Horiuchi, Junjiro; Saitoe, Minoru
Key points During olfactory aversive conditioning in Drosophila, odour and shock information are delivered to the mushroom bodies (MBs) through projection neurons in the antennal lobes (ALs) and ascending fibres of the ventral nerve cord (AFV), respectively. Using an isolated cultured brain expressing a Ca2+ indicator in the MBs, we demonstrated that the simultaneous stimulation of the ALs and AFV establishes long‐term enhancement (LTE) in AL‐induced Ca2+ responses. The physiological properties of LTE, including associativity, input specificity and persistence, are highly reminiscent of those of olfactory memory. Similar to olfactory aversive memory, LTE requires the activation of nicotinic acetylcholine receptors that mediate the AL‐evoked Ca2+ response, NMDA receptors that mediate the AFV‐induced Ca2+ response, and D1 dopamine receptors during the simultaneous stimulation of the ALs and AFV. Considering the physiological and genetic analogies, we propose that LTE at the AL–MB synapse can be a relevant cellular model for olfactory memory. Abstract In Drosophila, the mushroom body (MB) is a critical brain structure for olfactory associative learning. During aversive conditioning, the MBs are thought to associate odour signals, conveyed by projection neurons (PNs) from the antennal lobe (AL), with shock signals conveyed through ascending fibres of the ventral nerve cord (AFV). Although synaptic transmission between AL and MB might play a crucial role for olfactory associative learning, its physiological properties have not been examined directly. Using a cultured Drosophila brain expressing a Ca2+ indicator in the MBs, we investigated synaptic transmission and plasticity at the AL–MB synapse. Following stimulation with a glass micro‐electrode, AL‐induced Ca2+ responses in the MBs were mediated through Drosophila nicotinic acetylcholine receptors (dnAChRs), while AFV‐induced Ca2+ responses were mediated through Drosophila NMDA receptors (dNRs). AL–MB synaptic transmission was enhanced more than 2 h after the simultaneous 'associative‐stimulation' of AL and AFV, and such long‐term enhancement (LTE) was specifically formed at the AL–MB synapses but not at the AFV–MB synapses. AL–MB LTE was not induced by intense stimulation of the AL alone, and the LTE decays within 60 min after subsequent repetitive AL stimulation. These phenotypes of associativity, input specificity and persistence of AL–MB LTE are highly reminiscent of olfactory memory. Furthermore, similar to olfactory aversive memory, AL–MB LTE formation required activation of the Drosophila D1 dopamine receptor, DopR, along with dnAChR and dNR during associative stimulations. These physiological and genetic analogies indicate that AL–MB LTE might be a relevant cellular model for olfactory memory.